PENGARUH KOMPOSISI MEDIA TANAM DAN PUPUK SP36 TERHADAP PERTUMBUHAN TANAMAN GLADIOL (Gladiolus hybridus. L) - Ninggar Listiana; Nawawi Nawawi; Tatik Wardiyati (BUANA SAINS, 2010)
Gladiol is one of importance cut flower with high economic value due to beautiful kinds and colors. The aims of this research is to improved growth and flower quality of gladiola. Polibag experiment was conducted during December 2007 to February 2008 at Green house Faculty of Agriculture University of Brawijaya. Randomized Factorial Block Design and three (3) replication was applied with two factors. First factors consists of four planting media (hust cole, cocopeat, cocopeat + hust cole (4 : 1), cocopeat + hust cole (1 : 4) and second factor was three levels of SP36 ( 4, 8 and 12 g/polibag). The result showed that there is an interaction between media and fosfat fertilizer only on number of leaves, but did not on other parameters observed